Management of Laryngopharyngeal Reflux Around the World: An International Study. (17th November 2020) - Lechien, Jerome R.; Allen, Jacqueline E.; Barillari, Maria R.; Karkos, Petros D.; Jia, Huan; Ceccon, Fabio P.; Imamura, Rui; Metwaly, Osama; Chiesa‐Estomba, Carlos M.; Bock, Jonathan M.; Carroll, Thomas L.; Saussez, Sven; et al.
Abstract : Objective: To investigate worldwide practices of otolaryngologists in the management of laryngopharyngeal reflux (LPR). Methods: An online survey was sent on the management of LPR to members of many otolaryngological societies. The following aspects were evaluated: LPR definition, prevalence, clinical presentation, diagnosis, and treatment. Results: A total of 824 otolaryngologists participated, spread over 65 countries. The symptoms most usually attributed to LPR are cough after lying down/meal, throat clearing and globus sensation while LPR‐related findings are arytenoid erythema and posterior commissure hypertrophy. Irrespective to geography, otolaryngologists indicate lack of familiarity with impedance pH monitoring, which they attribute to lack of knowledge in result interpretation. The most common therapeutic regimens significantly vary between world regions, with a higher use of H2 blocker in North America and a lower use of alginate in South America. The duration of treatment also significantly varies between different regions, with West Asia/Africa and East Asia/Oceania otolaryngologists prescribing medication for a shorter period than the others. Only 21.1% of respondents are aware about the existence of nonacid LPR. Overall, only 43.2% of otolaryngologists believe themselves sufficiently knowledgeable about LPR. Conclusions: LPR knowledge and management significantly vary across the world. International guidelines on LPR definition, diagnosis, and treatment are needed to improve knowledge and management around the world. Level of Evidence: N.A. Laryngoscope, 131:E1589–E1597, 2021